Assess the Knowledge and Practice of Thalassemic Patient about Complications of Iron Overload and Desferal Compliance - Abdul Karim Ghanim (Iraqi National Journal of Nursing Specialties, 2008)
Objectives: To assess the knowledge and practice of thalassemic patients about desferal administration and complications of iron overload. Methodology: The present study composed of (50) thalssemic patient who are registered in center and was performed in Ibn Al-Atheer center for congenital anemia for the period from 15/12/2006 to 1/4/2007. Results: The result of the study showed highly significant difference at (160.05) for knowledge of thalassemic patients and also appear highly significant difference at (P<O.O5) for practice of thalassemic patients. Recommendations: The study recommends that there is necessity to increase the knowledge and practice of thalassemic patient about desferal administration to minimize the complications of iron overload.